New thoughts on the trade of lapis lazuli in the ancient near east : c. 3000 - 2000 B.C. - Ajango, Kelsey Michal (My University, 2010)
The trade of lapis lazuli in the ancient Near East has been one of continuous interest over the past forty years. It has been theorized that the semi-precious stone, which occurs naturally in modern-day Afghanistan, reached its destinations throughout the Near East by various trade networks. However, many of these theorized routes do not include recent excavations. Therefore, the goal of this study was to attempt to find new or substantiate existing claims of lapis lazuli trade routes through the analysis of textual evidence and recent excavations, namely the sites of Tell Brak, Tal-i Malyan, Tarut Island, and el-TOd. Whereas each site was a participant in the trade of lapis lazuli due to the mere presence of the stone, each city played a different role in its trade. However, the most compelling conclusion of this study is the possibility of a trade route by sea originating in the Indus Valley.
Keywords: Lapus lazuli -- Middle East -- History.; Middle East -- Commerce -- History.